Phylogenomic Analysis of Lactobacillus curvatus Reveals Two Lineages Distinguished by Genes for Fermenting Plant-Derived Carbohydrates. (29th May 2018) - Terán, Lucrecia C; Coeuret, Gwendoline; Raya, Raúl; Zagorec, Monique; Champomier-Vergès, Marie-Christine; Chaillou, Stéphane
Abstract: Lactobacillus curvatus is a lactic acid bacterium encountered in many different types of fermented food (meat, seafood, vegetables, and cereals). Although this species plays an important role in the preservation of these foods, few attempts have been made to assess its genomic diversity. This study uses comparative analyses of 13 published genomes (complete or draft) to better understand the evolutionary processes acting on the genome of this species. Phylogenomic analysis, based on a coalescent model of evolution, revealed that the 6, 742 sites of single nucleotide polymorphism within the L. curvatus core genome delineate two major groups, with lineage 1 represented by the newly sequenced strain FLEC03, and lineage 2 represented by the type-strain DSM20019. The two lineages could also be distinguished by the content of their accessory genome, which sheds light on a long-term evolutionary process of lineage-dependent genetic acquisition and the possibility of population structure. Interestingly, one clade from lineage 2 shared more accessory genes with strains of lineage 1 than with other strains of lineage 2, indicating recent convergence in carbohydrate catabolism. Both lineages had a wide repertoire of accessory genes involved in the fermentation of plant-derived carbohydrates that are released from polymers of α/β-glucans, α/β-fructans, and N-acetylglucosan. Other gene clusters were distributed among strains according to the type of food from which the strains were isolated. These results give new insight into the ecological niches in which L. curvatus may naturally thrive (such as silage or compost heaps) in addition to fermented food.